2020
DOI: 10.3390/polym12102369
|View full text |Cite
|
Sign up to set email alerts
|

A Constitutive Model of High-Early-Strength Cement with Perlite Powder as a Thermal-Insulating Material Confined by Caron Fiber Reinforced Plastics at Elevated Temperatures

Abstract: A parabolic stress–strain constitutive model for inorganic thermal-insulating material confined by carbon fiber-reinforced polymer (CFRP) exposed to a surrounding elevated temperature was proposed in this paper. The thermal-insulating material used in this study was composed of high-early-strength cement (HESC) and perlite powder. The compression strengths of four kinds of perlite powder composition ratios of thermal-insulating materials cylindrical specimens which were confined by one, two, and three-layer CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The overall residuals on all the tension data are evaluated and presented in Figure 9. The value corresponding to the sum of squared errors (SSE) is 3.0686 × 10 −4 using Equation (8). The SSE is given as…”
Section: Temperature Dependence Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall residuals on all the tension data are evaluated and presented in Figure 9. The value corresponding to the sum of squared errors (SSE) is 3.0686 × 10 −4 using Equation (8). The SSE is given as…”
Section: Temperature Dependence Modelingmentioning
confidence: 99%
“…By compounding different filler materials with polymer, new functional materials can be made, providing a viable technology for on-demand material design and engineering [ 1 ]. Applications of PBMs include, but are not limited to, polymer-bonded magnetics [ 2 , 3 ], energetics [ 4 , 5 ], aluminum [ 6 ], fiber [ 7 , 8 ], and many others [ 9 , 10 , 11 ]. To utilize those functional materials in critical applications, understanding their mechanical properties and deformation behaviors under different loading and temperature conditions is of great importance in meeting the basic design criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Razvi and Saatcioglu (1998) proposed a constraint equation for high-strength concrete [29]. Li's research proposed the constitutive models for normal-strength and low-strength cylindrical concrete confined with CFRP, which was adopted from the Mohr-Coulomb failure theory to predict the compressive strength of CFRP-confined concrete [30][31][32][33][34]. Wang et al (2012) found that the CFRP-confined-squarecross-section column failed suddenly via CFRP rupture at the corner of the column, and a modified confinement pressure model was proposed which considered the influence of cross-section size, effective rupture strain of CFRP, as well as hoop reinforcement [35].…”
Section: Introductionmentioning
confidence: 99%